Salivary Oxytocin Concentrations in Males following Intranasal Administration of Oxytocin: A Double-Blind, Cross-Over Study. - Katie Daughters; Antony S R Manstead; Kelly Hubble; Aled Rees; Anita Thapar; Stephanie H M van Goozen (PLoS ONE)
The use of intranasal oxytocin (OT) in research has become increasingly important over the past decade. Although researchers have acknowledged a need for further investigation of the physiological effects of intranasal administration, few studies have actually done so. In the present double-blind cross-over study we investigated the longevity of a single 24 IU dose of intranasal OT measured in saliva in 40 healthy adult males. Salivary OT concentrations were significantly higher in the OT condition, compared to placebo. This significant difference lasted until the end of testing, approximately 108 minutes after administration, and peaked at 30 minutes. Results showed significant individual differences in response to intranasal OT administration. To our knowledge this is the largest and first all-male within-subjects design study to demonstrate the impact of intranasal OT on salivary OT concentrations. The results are consistent with previous research in suggesting that salivary OT is a valid matrix for OT measurement. The results also suggest that the post-administration 'wait-time' prior to starting experimental tasks could be reduced to 30 minutes, from the 45 minutes typically used, thereby enabling testing during peak OT concentrations. Further research is needed to ascertain whether OT concentrations after intranasal administration follow similar patterns in females, and different age groups.